'My Attitude to Sport Is Very Simple – It's Something That Jews Just Don't Do': The Lost (?) World of Sport in Jewish Manchester. Issue 2 (1st September 2022) - Dee, David
Abstract: Reflecting on his childhood in post-war Manchester, Howard Jacobson claimed in 2016: 'I never met a Jew that wanted to play a sport, and the only Jew I ever met who did was me and that sport was table tennis . . . My attitude towards sport is simple – it's something that Jews just don't do'. This article explores sporting participation and interest within Manchester Jewry from the 1890s through to the modern day. It begins by mapping and analysing the strong sporting culture that developed before World War Two, a time when sport was actively promoted by communal leaders and when young Jews, in particular, took it to their heart. It moves on to show how, by the time Jacobson was growing up, it had indeed lost its centrality. Yet sport had not, as Jacobson may have claimed, disappeared from Manchester Jewry. Rather, it had changed, morphing into something which sat more comfortably with a more comfortable, middle-class community who had largely left the inner city behind. As they now occupied Manchester's margins, so too did sport move to occupy the margins of their new, changed realities.